The iron flower - Forest, Laurie; OverDrive, Inc. (Toronto, Ontario : Harlequin Teen, 2018)
"Elloren Gardner and her friends were only seeking to right a few wrongs when they rescued a Selkie and freed a military dragon. The last thing they expected was to be thrust into a realm-wide underground resistance against Gardnerian conquest. While the Resistance struggles to fight back against the harsh rulings of the Mage Council, more and more Gardnerian soldiers descend upon the University, led by none other than Lukas Grey, now commander of the nearby military base. Though Elloren tries to keep him at arm's length, Lukas is determined to tie himself to her, still convinced that she is the heir to the power of the Black Witch, a legacy of magic that will decide the future of all Erthia. As his own magic calls out to her, seeking to awaken a dark force within, Elloren finds it more and more difficult to believe that she's truly powerless, as her uncle always claimed. Caught between her growing feelings for the rebellious Yvan Guriel and the seductive power offered by Lukas, Elloren must find a way to stay true to what she knows is right and protect everyone she loves, even if that means protecting them from herself."--Amazon.com.
Sequel to: The Black Witch.
Electronic book.
Electronic reproduction.
Keywords: Advantage title -- Fiction; Witches -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Dragons -- Fiction; Magic -- Fiction; Government, Resistance to -- Fiction; Fantasy; Witches -- Fiction; JUVENILE FICTION -- Science Fiction, Fantasy, Magic; Dragons; Government, Resistance to; Imaginary wars and battles; Magic; Witches; Witches -- Juvenile fiction; Magic -- Juvenile fiction; Imaginary wars and battles -- Juvenile fiction; Witches -- Fiction; Magic -- Fiction; Imaginary wars and battles -- Fiction; Juvenile works; Novels; Fantasy fiction; Electronic books; Fantasy fiction; Young adult fiction